2016
DOI: 10.5964/ejop.v12i4.909
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between neurocognitive functioning and occupational functioning in bipolar disorder: A literature review

Abstract: Neurocognitive impairment in Bipolar Disorder (BD) has been widely reported, even during remission. Neurocognitive impairment has been identified as a contributing factor towards unfavourable psychosocial functioning within this population. The objective of this review was to investigate the association between neurocognitive impairment and occupational functioning in BD. A literature review of English-language journal articles from January 1990 to November 2013 was undertaken utilising the PsychINFO, Scopus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 69 publications
2
34
0
Order By: Relevance
“…Most jobs require a degree of memory and attention, so, targeting these functions may benefit occupational performance. Nevertheless, it does not seem to be a simple and direct relation and other factors would be mediating this relationship .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Most jobs require a degree of memory and attention, so, targeting these functions may benefit occupational performance. Nevertheless, it does not seem to be a simple and direct relation and other factors would be mediating this relationship .…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, these cognitive domains seem to be important for achieving a good functional outcome. Moreover, as a whole, cognitive variables could positively contribute more than other sociodemographic or clinical variables to occupational functioning . Most jobs require a degree of memory and attention, so, targeting these functions may benefit occupational performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the occupational expression, studies have reported illness history as one of its predictors, pointing out that a better clinical course indicates better occupational functioning 56 . Another variable that can partially explain the work disability found in this population is neurocognition, as it is known for subserving complex, abstract, and everyday processing 57 . Consequently, individuals would benefit from targeted vocational rehabilitation programs with tailored cognitive remediation, helping them avert similar future dismissals and improve their outcomes 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment has traditionally sought to reduce the effects of depression and mania. Moreover, even when symptomatic recovery is achieved, significant functional deficiencies often persist . Pharmacological treatment options to control symptoms and prevent relapse include lithium (Li), anticonvulsants, atypical antipsychotics, and antidepressants.…”
Section: Discussionmentioning
confidence: 99%